Fabrication of CMC-g-PAM Superporous Polymer Monoliths via Eco-Friendly Pickering-MIPEs for Superior Adsorption of Methyl Violet and Methylene Blue - Wang, Feng; Zhu, Yongfeng; Wang, Wenbo; Zong, Li; Lu, Taotao; Wang, Aiqin (Frontiers in Chemistry, 2017)
A series of superporous carboxymethylcellulose-graft-poly(acrylamide) (CMC-g-PAM) polymer monoliths presenting interconnected pore structure and excellent adsorption properties were prepared by one-step free-radical grafting polymerization reaction of CMC and acrylamide (AM) in the oil-in-water (O/W) Pickering-medium internal phase emulsions (Pickering-MIPEs) composed of non-toxic edible oil as a dispersion phase and natural Pal nanorods as stabilizers. The effects of Pal dosage, AM dosage, and co-surfactant Tween-20 (T-20) on the pore structures of the monoliths were studied. It was revealed that the well-defined pores were formed when the dosages of Pal and T-20 are 9-14% and 3%, respectively. The porous monolith can rapidly adsorb 1585 mg/g of methyl violet (MV) and 1625 mg/g of methylene blue (MB). After the monolith was regenerated by adsorption-desorption process for 5 times, the adsorption capacities still reached 92.1% (for MV) and 93.5% (for MB) of the initial maximum adsorption capacities. The adsorption process was fitted with Langmuir adsorption isotherm model and pseudo-second-order adsorption kinetic model very well, which indicate that mono-layer chemical adsorption mainly contribute to the high-capacity adsorption for dyes. The superporous polymer monolith prepared from eco-friendly Pickering-MIPEs shows good adsorption capacity and fast adsorption rate, which is potential adsorbent for the decontimination of dye-containing wastewater.